Microbial enhancement of plant aluminum tolerance - Cheng, Lang; Liu, Qi; Nian, Hai; Hartmann, Martin; Tran, Lam-Son Phan; Galindo-Castañeda, Tania; Lian, Tengxiang (Biology and fertility of soils, 2025)
Aluminum (Al) toxicity is a major limiting factor for crop production in acidic soils. The diverse mechanisms by which microbes enhance plant tolerance to Al toxicity, such as Al ion absorption, regulation of metal ion transport, adjustment of rhizosphere pH, filtration of Al ions through mycelial networks, and interaction with root traits, have attracted increasing attention. In this review, we focus on the physiological and biochemical effects of Al toxicity on plants, as well as the mechanisms of plant resistance to Al toxicity. We particularly emphasize the interaction between plants and microorganisms, and how microbes could be used to enhance plant tolerance to Al toxicity. Notably, microbial inoculation strategies often face challenges due to the soil properties and competitive exclusion by indigenous soil microbiomes. Despite these challenges, we propose that combining omics techniques with synthetic microbial consortia designed for Al stress may be a more effective approach to addressing the related issues in this research area. These advancements will pave the way for harnessing microbiome engineering as a powerful tool to enhance agricultural production and optimize practices in Al-challenged environments.